La religiosidad posmoderna: nihilismo, individualismo y religión a la carta = Postmodern Religiosity: Nihilism, Individualism, and Customized Religion - Porcel Moreno, Manuel (Cauriensia, 2024)
This paper intends to show how the "revival of the religious" does not so much signify a return of universal religions, but rather a "dissemination" or "decomposition" of these into countless mystical-exoteric mutations that lead to a "customized religion". Materialism, nihilism, and individualism characteristic of postmodern culture and society contribute to the creation of a "private religion" where all religious experience is relegated to the private realm of individual consciousness. Undoubtedly, this pseudo-religious postmodern context poses a challenge for the major traditional religious institutions, which will need to respond with sufficient adaptability to the "accelerated mobility of change" imposed by postmodern societies.